The Harmonization of Administrative Regulatory Arrangements Toward Public Institutional Accountability in Handling Cybercrime in Indonesia: Harmonisasi Penataan Regulasi Administratif terhadap Akuntabilitas Lembaga Publik dalam Penanganan Cybercrime di Indonesia - MS, Nuruzzaman; Fatimah, Siti (Mendapo: Journal of Administrative Law, 2025)
The rapid development of information technology has brought both positive impacts and significant challenges to public governance, particularly in addressing digital crimes (cybercrime). In Indonesia, the handling of cybercrime is not solely within the domain of criminal law but also requires the active involvement of state institutions within the framework of administrative law. Institutions such as the Ministry of Communication and Digital Affairs (Komdigi), the National Cyber and Crypto Agency (BSSN), as well as other agencies like the Indonesian National Police (Polri) and the Attorney General's Office, play strategic roles in maintaining the security and order of the national digital space. However, bureaucratic realities reveal persistent issues, including overlapping authorities, weak inter-agency coordination, and suboptimal implementation of administrative functions. Therefore, the harmonization and synchronization of administrative regulations have become urgent to ensure policy alignment, clear division of institutional responsibilities, and the reinforcement of transparency and accountability principles in digital governance. This article aims to analyze how the harmonization and synchronization of administrative regulations can enhance the accountability of public institutions in addressing digital crimes in Indonesia, using a normative juridical approach and descriptive-analytical methods.